PHYSIOLOGICAL INDICES AND GROWTH OF ‘PALUMA’ GUAVA UNDER SALINE WATER IRRIGATION AND NITROGEN FERTIGATION - Idelfonso Leandro Bezerra; Reginaldo Gomes Nobre; Hans Raj Gheyi; Geovani Soares De Lima; Joicy Lima Barbosa (Revista Caatinga, 2018)
The cultivation of irrigated guava in semi-arid areas highlights the need for information regarding its responses to irrigation water quality and the fertilization management that enables its exploitation. Thus, this study aimed to evaluate the effect of water salinity and nitrogen (N) doses on the growth and physiology of the guava cv. ‘Paluma’. The experiments was conducted in drainage lysimeters under field conditions in an experimental area at the Center of Sciences and Agri-Food Technology of the Federal University of Campina Grande (CCTA/UFCG), Campus II, in Pombal, PB, Brazil. The experiment had a randomized block design, and treatments consisted of a 5 x 4 factorial arrangement corresponding to five levels of irrigation water electrical conductivity, ECw (0.3, 1.1, 1.9, 2.7, and 3.5 dS m-1), and four N doses (70, 100, 130, and 160% of the recommended N dose). The 100% dose corresponded to 541.1 mg of N dm-3 of soil. Increments in irrigation water salinity from 0.3 dS m-1 led to a reduction in stomatal conductance, internal CO2 concentration, CO2 assimilation rate, transpiration, instantaneous water use efficiency, the number of leaves and branches, stem diameter, and absolute and relative growth rates. Nitrogen doses ranging from 378.7 to 865.7 mg of N dm-3 of soil did not affect gas exchange and plant growth. Although ‘Paluma’ guava growth was affected by increases in water salinity, these plants can be irrigated using water of up to 1.42 dS m-1 with an acceptable reduction of 10% in growth variables. The interaction between irrigation water salinity and N fertilization had no significant effect on any of the variables studied.